Elaborasi Teknik Permainan dan Penyajian Uptown Funk Karya Mark Ronson Pada Saxofon - Damanik, Yogi Martua; Manalu, Kartini; Sihombing, Nielson (Innovative: Journal Of Social Science Research, 2025)
This thesis discusses the elaboration of playing techniques and presentation of the saxophone in the work Uptown Funk by Mark Ronson. The techniques used are diaphragmatic breathing, tonguing, altissimo, staccato, and improvisation. This research also provides an explanation of the difficulties experienced by the author when presenting this work in a recital. In the final part, the author explains the presentation of Uptown Funk during a recital. The result of the training is that the author is able to use the techniques that the author has prepared in presenting the repertoire and at the recital the author uses these techniques well as previously trained.